2021
DOI: 10.1530/eje-20-1439
|View full text |Cite
|
Sign up to set email alerts
|

MECHANISMS IN ENDOCRINOLOGY: Human brown adipose tissue as a therapeutic target: warming up or cooling down?

Abstract: Excessive accumulation of white adipose tissue leads to obesity and its associated metabolic health consequences such as type 2 diabetes and cardiovascular disease. Several approaches to treat or prevent obesity including public health interventions, surgical weight loss, and pharmacological approaches to reduce caloric intake have failed to substantially modify the increasing prevalence of obesity. The (re-)discovery of active brown adipose tissue (BAT) in adult humans approximately 15 years ago led to a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 166 publications
(253 reference statements)
0
32
0
1
Order By: Relevance
“…Among the many roles that WAT plays in physiology, its role as an energy store during cold treatment is critical for directing lipids toward BAT for thermogenesis. The response of adipose tissue to cold demonstrates the highly dynamic and elastic nature of this tissue [ 9 , 14 , 19 ]. For instance, when exposed to extended cold treatment, WAT differentiates into beige/brite adipocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many roles that WAT plays in physiology, its role as an energy store during cold treatment is critical for directing lipids toward BAT for thermogenesis. The response of adipose tissue to cold demonstrates the highly dynamic and elastic nature of this tissue [ 9 , 14 , 19 ]. For instance, when exposed to extended cold treatment, WAT differentiates into beige/brite adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…WAT primarily functions as a lipid storage tissue and is the primary source of energy, particularly during fasting [ 13 ]. In contrast, BAT plays a major role in regulating energy expenditure during cold exposure by enhancing mitochondrial heat production via a nonshivering mechanism [ 9 , 14 ]. Bartelt et al reported that short-term cold exposure results in increased BAT activity, which enhances TG uptake in a process that relies on LPL enzyme activity [ 15 ].As the ANGPTL protein family members are important regulators of TG metabolism in the adipose tissue, several studies have focused on the role of ANGPTL4 in cold treatment [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adipose tissue response to cold demonstrates the elasticity and the highly dynamic state this tissue possesses [11,14,19]. This is clearly shown in the WAT tissue response to extended cold treatment where it can be differentiated into what is called beige or brite adipocytes [11,14,19]. Like BAT, beige cells exhibit a high level of UCP1 and many mitochondria with high thermogenetic capacity.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, brown adipocytes are a powerhouse that consumes a large amount of energy which can enhance energy expenditure and alleviates insulin resistance by creating a negative energy balance [11][12][13]. Brown adipose tissue facilitates the mitochondrial heat production through a non-shivering mechanism that uncouples ATP production from substrate metabolism [11,14]. Moreover, shifting white adipocytes into brown or beige adipocytes is a eld of high value as it constitutes a mechanism to increase energy expenditure and enhance metabolic function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation